2022
DOI: 10.3389/fpsyg.2021.627575
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Effectiveness of the Health Belief Model in Predicting Preventive Behavior During the COVID-19 Pandemic: The Case of Romania and Italy

Abstract: We use a cultural psychology approach to examine the relevance of the Health Belief Model (HBM) for predicting a variety of behaviors that had been recommended by health officials during the initial stages of the COVID-19 lockdown for containing the spread of the virus and not overburdening the health system in Europe. Our study is grounded in the assumption that health behavior is activated based on locally relevant perceptions of threats, susceptibility and benefits in engaging in protective behavior, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
15
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 105 publications
(137 reference statements)
6
15
0
1
Order By: Relevance
“…A very small significance of susceptibility to the disease and the observed severity of the disease were obtained in an earlier study (Clark et al, 2020). Perceived barriers to preventive behavior were significant predictors of preventive behavior in other studies (Asmundson et al, 2001;Barakat & Kasemy, 2020;Karimy et al, 2021;Karl et al, 2021;Mahindarathne, 2021;Shahnazi et al, 2020;Shitu et al, 2022;Zewdie et al, 2022), as well as perceived benefits of preventive behavior (Barakat & Kasemy, 2020;Clark et al, 2020;Karimy et al, 2021;Karl et al, 2021;Mahindarathne, 2021;Vardavas et al, 2020;Zewdie et al, 2022). These results suggest that public information campaigns and the promotion of preventive health behavior in relation to COVID-19 should be designed to focus on clearly presenting the benefits that respondents derive from such behavior, as well as on reducing barriers to its implementation.…”
Section: Discussionmentioning
confidence: 76%
“…A very small significance of susceptibility to the disease and the observed severity of the disease were obtained in an earlier study (Clark et al, 2020). Perceived barriers to preventive behavior were significant predictors of preventive behavior in other studies (Asmundson et al, 2001;Barakat & Kasemy, 2020;Karimy et al, 2021;Karl et al, 2021;Mahindarathne, 2021;Shahnazi et al, 2020;Shitu et al, 2022;Zewdie et al, 2022), as well as perceived benefits of preventive behavior (Barakat & Kasemy, 2020;Clark et al, 2020;Karimy et al, 2021;Karl et al, 2021;Mahindarathne, 2021;Vardavas et al, 2020;Zewdie et al, 2022). These results suggest that public information campaigns and the promotion of preventive health behavior in relation to COVID-19 should be designed to focus on clearly presenting the benefits that respondents derive from such behavior, as well as on reducing barriers to its implementation.…”
Section: Discussionmentioning
confidence: 76%
“…We used a broad definition of perceptions about barriers to adherence, such as work outside the home and need for childcare, and found that these were of prime importance in the family cohort but not the older adult cohort. Though meta-analyses of HBM constructs have found perceived barriers to be the most consistently powerful of the model’s constructs [ 48 ], the COVID-19 literature on protective behaviors reflects our mixed findings [ 37 , 43 , 44 ]. Having a child in daycare or school and leaving the home for work could expose a person to more interactions during transit to childcare/work locations, make them more likely to complete errands once already out, or make the perceived risk of additional contacts beyond those from childcare/work to be negligible by comparison.…”
Section: Discussionmentioning
confidence: 92%
“…First, the higher willingness among those who have been immunized against COVID-19 can be explained by the psychological domain gradient of the Health Belief Model. (42) Immunized individuals often have a higher perceived susceptibility to and severity of the disease, as well as an understanding of the bene ts of preventive measures. Therefore, they are more motivated to engage in other infection-prevention measures, such as voluntary testing for COVID-…”
Section: Discussionmentioning
confidence: 99%